2013
DOI: 10.1155/2013/760685
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efficiency of Dye‐Sensitized Solar Cell by High Surface Area Anatase‐TiO2‐Modified P25 Paste

Abstract: How to improve the conversion efficiency and the stability of dye-sensitized solar cells (DSSCs) are two major problems. Furthermore, reduction of the manufacturing cost of DSSCs and large-scale manufacture are also very important factors. As a raw material, commercial P25 would be used for large-scale manufacture of TiO2paste with simple preparation procedure. However, there are several drawbacks for P25 such as the low surface area of P25 powder and the poor connectivity among particles in film using traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…comparing with other groups using experimental technique like the open-circuit voltage decay (OCVD) [4,23], the calculated time constants are approximately in the same order. It is interesting to note that the cell containing spacer thickness of 30 m gives the highest lifetime ( ) value as seen in Table 4.…”
Section: Electrochemical Impedance Spectroscopysupporting
confidence: 62%
See 2 more Smart Citations
“…comparing with other groups using experimental technique like the open-circuit voltage decay (OCVD) [4,23], the calculated time constants are approximately in the same order. It is interesting to note that the cell containing spacer thickness of 30 m gives the highest lifetime ( ) value as seen in Table 4.…”
Section: Electrochemical Impedance Spectroscopysupporting
confidence: 62%
“…This provides not only large surface area for the adsorption of dyes for light harvesting, but also a network for electron transport to the FTO glass substrate and subsequently to the external circuit. Thus, the different parameters of the TiO 2 photoanode, such as particle size, thickness, and the surface area, play important roles in the performance of DSSC [4]. A lot of studies have been performed to enhance or arrive at optimum efficiency of DSSC depending on the semiconductor active layer [5][6][7][8][9][10][11][12], the type of dye [13,14], the composition and concentration of electrolyte [13,15,16], and the type and thickness of counter electrode [17][18][19][20][21].…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TiO 2 loading with Au was produced by the impregnation method which is a very simple technique and does not require The specific surface area (SSA BET ) of the TiO 2 and Auloaded TiO 2 nanoparticles was found to be in the range of 69-109 m 2 g −1 with the particle diameter in the range of 14-21 nm, corresponding well with the XRD results. It was reported that high surface area of TiO 2 active layer has many advantages such as large amount of dye adsorption, high light-harvesting efficiency, rapid electron transport, and low electron recombination [38][39][40]. Therefore, high photoefficiency could be expected.…”
Section: Synthesis and Characterization Of Au-loaded Tiomentioning
confidence: 99%
“…Dye-sensitized solar cells (DSSCs) have remained one of the most promising choices for the realization of low-cost solar cells; it has, in the recent years, attracted remarkable attention owing to simplicity of its fabrication process and low manufacturing cost with excellent light absorbing materials [1][2][3]. Nevertheless, the power conversion efficiency (PCE) of the device has barely gone up to 11.9 % [4].…”
Section: Introductionmentioning
confidence: 99%